KEBERHASILAN KEGIATAN CORPORATE SOCIAL RESPOSIBILITY MELALUI PENGUNGKAPAN DAN AUDIT CORPORATE SOCIAL RESPOSIBILITY - Sri Fadilah (Jurnal Telaah dan Riset Akuntansi, 2009)
CSR is perceived as an activity undertaken by the company's donations (corporate philanthropy), while widely CSR is essentially a mechanism for integrating social issues and environmental issues into company operations and then communicate with stakeholders (stakeholders). In that sense, CSR is regarded as a new strategic framework to enhance competitiveness and achieve sustainable business. CSR Audit gives an overview of the audit framework for CSR programs. Aspects in the tables were developed based on the definition of CSR that have been formulated, as a: Concerns that companies set aside some of the profits (profit) for the benefit of human development (people) and environmental (planet) in a sustainable manner based on the procedure (procedure) an appropriate and professional. For this reason, in order to improve its CSR activities in accordance with the spirit of the meaning of an effort to fulfill its corporate social responsibility, the disclosure and auditing of CSR activities are very important. For this reason this paper with all its drawbacks tried to explain how the disclosure of CSR in which the related audit report also describes CSR CSR in order to improve the effectiveness of CSR activities.         Keywords: Corporate Social Responsibility, CSR Disclosure and Audit